Relationship Between Sensory Processing Patterns and Critical Thinking in Students - Seyed Sadegh Salehi Sadati; Atieh Hasani Helm; Zahra Mortazavi; Behnaz Alafchi; Homa Naderifar; Saideh Sadat Mortazavi (Strides in Development of Medical Education, 2022)
Background: Sensory processing pattern is a unique characteristic in each human. Critical thinking is a well-known skill of successful individuals.Objectives: This study aimed to investigate the correlation between the critical thinking skills and sensory processing patterns of students of Medical Sciences.Methods: This cross-sectional study was conducted on 213 students (147 males and 66 females). Brown’s Adolescent and Adult Sensory Profile Questionnaire and Ricketts’ Critical Thinking Questionnaire were used for data collection. Data analysis was performed using SPSS software (version 24) and appropriate statistical tests (i.e., the Pearson correlation test and independent samples t-test).Results: Critical thinking had a significant positive relationship with sensory sensitivity (r=0.229) and a significant inverse relationship with sensory seeking (r=-0.249) and low registration (r=-0.223). Critical thinking had a significant positive relationship with students’ grade point average (r=0.875). Additionally, there was no significant relationship between critical thinking with sensory avoidance (r=0.099) and age (r=0.847). In the sensory processing patterns, only low registration had a significant relationship with gender (P<0.05).Conclusion: Students whose dominant patterns of sensory processing were sensory sensitivity and sensory seeking had better and worse critical thinking skills than others, respectively. It seems necessary to pay attention to sensory processing patterns in students to develop their mental skills, especially critical thinking.